2021
DOI: 10.1002/suco.202100470
|View full text |Cite
|
Sign up to set email alerts
|

Compressive behavior of precast concrete sandwich panels containing recycled tyre crumb rubber core

Abstract: This paper presents the structural behavior of precast concrete sandwich panels (PCSPs) containing recycled tyre crumb rubber core under uni‐axial compression and compared with that containing commonly used expanded polystyrene (EPS) foam. A total of six panels were cast and tested. Two for each category of precast concrete panels that is, solid concrete panel, crumb rubber sandwich panel and foam sandwich panel. Results showed that the ultimate axial load of crumb rubber sandwich panel was found to be 91% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Marani et al [18] used phase changing material as a core and evaluated the thermal performance. Awan and Shaikh [19] have tried using a crumb rubber core in sandwich panels and found that the crumb rubber core improved the ultimate strength. Castillo-Laro et al [20] have studied the performance of sandwich panel with reinforced foam concrete core.…”
Section: Truss Shear Section X-xmentioning
confidence: 99%
“…Marani et al [18] used phase changing material as a core and evaluated the thermal performance. Awan and Shaikh [19] have tried using a crumb rubber core in sandwich panels and found that the crumb rubber core improved the ultimate strength. Castillo-Laro et al [20] have studied the performance of sandwich panel with reinforced foam concrete core.…”
Section: Truss Shear Section X-xmentioning
confidence: 99%
“…This sandwich panel is similar in size and configuration to FSP except that the core material is replaced with F I G U R E 1 Details of solid concrete panel (All dimensions are in mm) 44 recycled tire crumb rubber as shown in Figure 3. The recycled tire crumb rubber sheets are readily available in commercial warehouse in 1000 mm  1000 mm  20 mm size and are locally procured.…”
Section: Crumb Rubber Sandwich Panel (Crsp)mentioning
confidence: 99%
“…Details of precast concrete sandwich panel (All dimensions are in mm)44 F I G U R E 3 Crumb rubber used as core material F I G U R E 4 Recycle tire crumb rubber with steel reinforcement44 …”
mentioning
confidence: 99%
“…This is particularly relevant, given that prefabrication of elements and the automation of on-site construction techniques are recognized as fundamental requirements to ensure the economic, social, and environmental sustainability of the building sector, both for new constructions and renovations [54,55]. Moreover, several authors have addressed the issue of energy optimization of prefabricated building components, focusing on the selection of sustainable materials and the development of high-performance insulation solutions, including R-EPS [56][57][58][59][60]. These approaches consider the life cycle of the material and adopt principles of circular economy.…”
Section: Introductionmentioning
confidence: 99%